The influence of combine drive design parameters on corn grain harvesting efficiency - Khvostenko, D.; Gorbenko, O. (Scientific Progress & Innovations, 2025)
The article investigates the impact of design parameters of grain combine harvester drives on the productivity, efficiency, and quality of corn grain harvesting. Considering current requirements for agrotechnological processes, particular attention is paid to the type of power transmission, gear ratio, adaptability of control systems, and energy efficiency of the drives. The research was conducted under field test conditions using modified models of combine harvesters equipped with different types of drive systems: mechanical, hydraulic, and adaptive hydraulic. The conducted analysis proves that the design parameters of the drive system significantly influence the technical and operational performance during corn harvesting. Specifically, parameters such as transmission type, gear ratio, adaptability, and energy efficiency determine the operational stability, grain loss rate, fuel consumption, and the quality of grain cleaning. The study results showed that the most effective system is the adaptive hydraulic drive, which ensures productivity of 33.2 t/h, minimizes grain losses to 0.6%, and reduces specific fuel consumption to 1.5 L/t. Mathematical analysis revealed a high degree of correlation between productivity and grain losses, cleaning quality, and energy consumption, confirming the advisability of improving drives in the direction of flexible mode regulation. The scientific novelty of the work lies in identifying a quantitative relationship between the drive type and the combine's comprehensive efficiency indicators, justifying the implementation of adaptive hydraulic systems in harvesting machinery. The practical significance of the study lies in the possibility of applying the obtained results for modernizing the existing fleet of machines and developing new technical solutions aimed at increasing productivity and reducing energy consumption in the grain harvesting process. The obtained results can serve as a basis for improving the existing designs of grain harvesters and for developing new adaptive drive systems that meet energy-saving, reliability, and high-quality technological process requirements.